DESAIN DAN IMPLEMENTASI SISTEM MONITORING TEGANGAN DAN ARUS MOTOR INDUKSI TIGA PHASE MENGGUNAKAN KONSEP INTERNET OF THINGS (IOT) - Heru Susanto; Agus Nurcahyo (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2018)
Monitoring for voltage and current in a three-phase induction motor that is widely used in industry needs to be carried out continuously to ensure that motor performance remains good. Utilizing the Internet of Things (IoT) can help carry out this monitoring task to minimize the existence of human error factors. Design and implementation of a system is needed to monitor voltage and current in a three phase induction motor using the IoT concept so that monitoring can be done anytime and anywhere as long as it is connected to the internet. This system design consists of hardware and software that works to monitor the voltage and current that comes from a three-phase induction motor. The hardware part consists of the NodeMCU+ESP8266 module, 16x2+I2C LCD module, ACS712 current sensor module, AC voltage sensor module, CD4051 analog IC multiplexer, and power supply. The software part is a program algorithm that contains a flow of voltage and current readings to be displayed on IoT services named Thingspeak. The appearance of the Thingspeak application is designed to present data readings of three-phase voltage sensors and readings of three-phase current sensors. The results of the research show that the system designed has been implemented to monitor voltage and current in an three-phase induction motor based on IoT. The data displayed in Thingspeak consists of three phase AC voltage and three phase AC current. The test results show the difference between the data on Thingspeak with a measuring device which is 1% for phase R voltage, 2% for S phase voltage, 1% for phase T voltage, 37% for phase R current, 7% for S phase current, and 13% for phase T current.